A sex-positive mixed methods approach to sexting experiences among college students. (February 2021) - Graham Holmes, Laura; Nilssen, A. Renee; Cann, Deanna; Strassberg, Donald S.
Abstract: Many adolescents and adults engage in sexting: the exchange of nude photos via cellular phones. Most sexting research focuses on associated health risks and negative outcomes ( e.g., privacy breaches), with less examination of positive sexting outcomes and the role sexting plays in intimate relationships. In this study, we elicited participants' evaluations of their sexting outcomes. College students ( N  = 1265) completed the anonymous online survey about sexting. The acts of sending, receiving, and forwarding sexts were considered separately. Content analysis and group comparisons were used to analyze data. A substantial proportion of participants reported sending and/or receiving sexts. Participants described a variety of outcomes, both positive ( e.g., relationship benefits, self-confidence) and negative ( e.g., receipt of unwanted sexts, guilt). Participant religiosity, and the relationship between sender and receiver ( e.g., committed relationship, online acquaintance), were among the factors that affected whether participants rated their sexting experiences as positive, neutral, or negative, and to perceived likelihood of future sexting. Sexting contributed to participants' relationships and identities in both positive and negative ways. The results highlight how the context ( e.g., cultural, relational, personal) of sexting is important for understanding perceived outcomes and future sexting behavior. Highlights: Participants reported a broad range of positive outcomes such as pleasure, relationship benefits, and enhanced confidence. They also reported a broad range of negative outcomes such as guilt, feeling disgusted or vulnerable due to unwanted sexts. Religious participants and those who had ever sexted outside of relationships rated sexting experiences as less positive. More women and LGBQ participants said that sending sexts resulted in positive self-assessments than men and heterosexuals. LGBQ participants had higher odds of identifying nonconsensual sexts as a negative outcome compared to heterosexuals.